The Effectiveness of Using Chain Story in Teaching Writing - Eka Dyah Puspita Sari; Ika Erawati (JELLE : Journal Of English Literature, Linguistics, and Education, 2020)
Some students find writing practice boring. It causes them less motivated to write in English. One of the ways to make students more motivated to write is by using games in teaching learning activity. One of the games is chain story. Magee (1993) states that chain story involves group story development. In other words, chain story is regarded useful to improve students’ writing skill. To find out the effectiveness of using chain story games in teaching writing is the main concern of this research. The research applied experimental method with quantitative approach in the analysis. The data were 24 students who worked as the experimental and control groups. The result of the research shows that chain story game is proven to be beneficial in teaching writing. It is supported with the data of students’ average score in post-test (73,46) is higher than students’ average score in pre-test (64,38). Keywords: chain story, experimental method, teaching writing